Popular Music in Esports, On and Beyond the Stage - Febrer-Coll, Eulalia (Intellect, 2026)
Esports’ success and their growing impact on popular culture have led to the development of an emphasis on their sonic and musical elements, afforded and brought in by developing companies, which are now frequently collaborating with international pop stars to increase their reach for wider audiences. This chapter explores the multiple ways in which popular music has come to intersect with esports as video games and part of the wider entertainment culture, using League of Legends as a case study to analyse how the diverse approaches explored can materialise under a specific title.
Keywords: esports; fortnite; in-game music; league of legends; ludomusicology; music events; music for video games; popular music; social media music; video games